710 Developing a Standardised Form to Improve Communications Between General Surgical Juniors and Microbiologists. (19th August 2022) - Edmonds, R; Jamadar, T; Coronelli, M; Weerasinghe, D; Ali, N; Magro, T
Abstract: Aim: To improve discussions between microbiology and surgical juniors. Method: As a group we identified that discussions with microbiology were documented in notes, but not easily found when further discussions were required. We also found that some discussions were more difficult if the junior did not have all of the appropriate information to hand. We created a separate form to document microbiology discussions, bring together the essential information that they required for the conversations and enable quick reference for future discussions. We sent out a questionnaire to assess the level of the difficulties, introduced the form and documented any additional information that was asked for during discussions. We then repeated the questionnaire to assess if there were any improvements. Results: The original version was insufficient, in that it was not distinct from other paper notes so could be difficult to find, and some questions were asked frequently that we did not have answers for. The discussions however were improved, and the recording of reasoning for decisions enabled more consistent recommendations. Conclusions: By creating the form we helped juniors prepare for more constructive calls to microbiology, were able to answer some of their questions regarding why prior decisions were made and at the end have the most sensible suggestions and plans from microbiology for surgical patients. While we still use paper notes, the concept and format are suitable for transfer to other specialities and electronic records where available.